Neurotrauma and the rule of rescue. Issue 12 (24th September 2011) - Honeybul, S; Gillett, G R; Ho, K M; Lind, C R P
Abstract : The rule of rescue describes the powerful human proclivity to rescue identified endangered lives, regardless of cost or risk. Deciding whether or not to perform a decompressive craniectomy as a life-saving or 'rescue' procedure for a young person with a severe traumatic brain injury provides a good example of the ethical tensions that occur in these situations. Unfortunately, there comes a point when the primary brain injury is so severe that if the patient survives they are likely to remain severely disabled and fully dependent. The health resource implications of this outcome are significant. By using a web-based outcome prediction model this study compares the long-term outcome and designation of two groups of patients. One group had a very severe injury as adjudged by the model and the other group a less severe injury. At 18 month follow-up there were significant differences in outcome and healthcare requirements. This raises important ethical issues when considering life-saving but non-restorative surgical intervention. The discussion about realistic outcome cannot be dichotomised into simply life or death so that the outcome for the patient must enter the equation. As in other 'rescue situations', the utility of the procedure cannot be rationalised on a mere cost–benefit analysis. A compromise has to be reached to determine at what point either the likely outcome would be unacceptable to the person on whom the procedure is being performed or the social utility gained from the rule of rescue intervention fails to justify the utilitarian value and justice of equitable resource allocation.